Exploring the causes and process of becoming child domestic worker - Chodhuary, Shuburna; Islam, Md. Akramul; Akter, Jesmin (BRAC Research and Evaluation Division, 2022)
The study aimed to explore the demographic and socioeconomic characteristics of households with and without Child Domestic Workers (CDW), and explore the causes and process of becoming CDWs in Bangladesh. Both quantitative and qualitative approaches were used to collect data. A purposive sampling technique was applied to select the sample locations. Data were collected from six districts of Bangladesh: Mymensingh, Kishoreganj, Jamalpur, Bhola, Kurigram, Chapai Nawabganj, and a slum of Dhaka city. A total of 1,564 (rural 1,454 and urban 110) parents of with and without CDWs were interviewed. Ten in-depth interviews with CDWs were conducted. The findings reveal that small income, poor savings, marginal land, less access to NGO services, and sickness of main income earner in the family were the causes that compelled parents to allow their children in CDW. The findings also strongly observed that poverty is the root cause to engage children in domestic work. Finally, it was also seen that neighbours, relatives, employers, and middlemen as the intermediary were effective and influential too for CDW in both the study areas. However, parents and CDW herself/himself in urban areas were the most instrumental factors to get into domestic work. Ensuring economic empowerment, educational facilities, health services, and raising awareness on child rights among the households with and without CDWs through BRAC programs could slow down children’s involvement in domestic work.